2020
DOI: 10.1177/0886260520903131
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Wife Beating Among Female and Male Adolescents in Jordan

Abstract: Previous research in the Middle East and North Africa has revealed justifying attitudes toward wife beating among adults but little is known about adolescent attitudes and its predictors. Therefore, the purpose of the present study was to examine theoretically relevant predictors of supportive attitudes toward wife beating among adolescents in Jordan. Due to limited evidence on the role of gender, potential differences between girls and boys were explored. A total of 856 students (455 female) from 14 secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…These findings are supported by prior studies. For example, a study of 14 secondary schools in Jordan found that the prevalence of justified wife-beating ranged between 6.1% -50.5% [17]. Ironically, we found that a higher proportion of young women accepted wife-beating compared to young men.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These findings are supported by prior studies. For example, a study of 14 secondary schools in Jordan found that the prevalence of justified wife-beating ranged between 6.1% -50.5% [17]. Ironically, we found that a higher proportion of young women accepted wife-beating compared to young men.…”
Section: Discussionmentioning
confidence: 48%
“…For instance, people who believe that IPV is acceptable are more likely to perpetrate it or be victimized [16]. Young people (persons between the ages of 10-24 years) are more likely to accept wife-beating, and mostly acquire the attitude from older generations, such as parents, through social learning [17][18][19][20][21]. Evidence suggest that men who were abused during childhood or witnessed paternal abuse against their mothers are more likely to accept wife-beating or become wife beaters [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Building mostly on cross-sectional data, previous studies have shown that the belief that physical and/or sexual violence in a relationship is normative and acceptable may make a person more vulnerable to be victimized by his or her partner (see Capaldi et al 2012;Vézina and Herbert 2007, for reviews). It has also been suggested that one of the origins of supportive attitudes toward IPV is the exposure to family violence through which individuals may adopt violent norms and scripts (e.g., Copp et al 2019;Schuster et al 2020). Further, McDonnell et al (2010 found that both female and male adolescents who held supportive attitudes toward violence and justified it, reported higher odds of dating victimization, based on a combined score of lifetime physical and emotional victimization in dating relationships.…”
Section: The Role Of Attitudes Toward Intimate Partner Violence (Ipv)mentioning
confidence: 99%
“…Inglehart and Norris (2003), in their analysis of the WVS, found a significant difference in attitude toward gender roles and gender equality between Muslim and non-Muslim groups. According to Schuster et al (2020), women are expected to be submissive to men and restrain their sexuality in the Middle East and North Africa. Furthermore, husbands in these regions exhibit a tolerant attitude toward wife beating when wives breach patriarchal culture (see also Zakar et al, 2013).…”
Section: Affiliation With Islam and Attitudes Toward Wife Beatingmentioning
confidence: 99%
“…Haj-Yahia (2003) observed that one's religiosity is an important element of patriarchal ideology. He found that religiosity was strongly and positively connected to an accepting attitude toward wife beating among Arab men in Israel (see also Schuster et al, 2020). However, researchers have shown that individual religiosity is related to a decreased attitude of acceptance toward wife beating (Jung & Olson, 2017) and other behaviors considered immoral, such as premarital sex (Jung, 2016), extramarital sex (Adamczyk & Hayes, 2012), prostitution (Finke & Adamczyk, 2008), and suicide ideation (Boyd & Chung, 2012).…”
Section: Country-level Factorsmentioning
confidence: 99%